Perbandingan karakteristik lingkungan pengendapan, batuan sumber, dan diagenesis Formasi Lakat di lereng timur laut dengan Formasi Talangakar di tenggara Pegunungan Tigapuluh, Jambi - Heryanto, Rachmat (Geological Agency, 2006)
http://dx.doi.org/10.17014/ijog.vol1no4.20061The Central Sumatera Basin and the Jambi Subbasin is separated by the Tigapuluh High. During Late Oligocene â€“ Middle Miocene, the Lakat Formation was deposited in fl uvial, fl ood plain associated with swamp, and tidal environments, whereas the Jambi Subbasin was occupied by the deposition of the Talangakar Formation in fl uvial and deltaic environments. The provenance of both formations was derived from the Tigapuluh and Barisan Mountain Highs. Diagenesis stage of the Talangakar Formation is higher (Mesogenetic mature B) than that of the Lakat Formation (Mesogenetic immature). This is because the Talangakar Formation was deposited within an unstable basin formed by horst, and graben structures which were still active during the deposition of the formation. On the other hand, the Lakat Formation was deposited in a more stable basin. Â Â